Geometric Morphometrics of Hominoid Infraspinous Fossa Shape. Issue 1 (January 2015) - Green, David J.; Serrins, Jesse D.; Seitelman, Brielle; Martiny, Amy R.; Gunz, Philipp; Terhune, Claire; Cooke, Siobhán B.; Laitman, Jeffrey T.
ABSTRACT Recent discoveries of early hominin scapulae from Ethiopia (Dikika, Woranso‐Mille) and South Africa (Malapa) have motivated new examinations of the relationship between scapular morphology and locomotor function. In particular, infraspinous fossa shape has been shown to significantly differ among hominoids. However, this region presents relatively few homologous landmarks, such that traditional distance and angle‐based methods may oversimplify this three‐dimensional structure. To more thoroughly assess infraspinous fossa shape variation as it relates to function among adult hominoid representatives, we considered two geometric morphometric (GM) approaches—one employing five homologous landmarks ("wireframe") and another with 83 sliding semilandmarks along the border of the infraspinous fossa. We identified several differences in infraspinous fossa shape with traditional approaches, particularly in superoinferior fossa breadth and scapular spine orientation. The wireframe analysis reliably captured the range of shape variation in the sample, which reflects the relatively straightforward geometry of the infraspinous fossa. Building on the traditional approach, the GM results highlighted how the orientation of the medial portion of the infraspinous fossa differed relative to both the axillary border and spine. These features distinguished Pan from Gorilla in a way that traditional analyses had not been able to discern. Relative to the wireframe method, the semilandmark approach further distinguished Pongo from Homo, highlighting aspects of infraspinous fossa morphology that may be associated with climbing behaviors in hominoid taxa. These results highlight the ways that GM methods can enhance our ability to evaluate complex aspects of shape for refining and testing hypotheses about functional morphology. Anat Rec, 298:180–194, 2015. © 2014 Wiley Periodicals, Inc.